Sailing into the future: technologies, challenges, and opportunities for maritime communication networks in the 6G era - Xylouris, Georgios; Nomikos, Nikolaos; Kalafatelis, Alexandros; Giannopoulos, Anastasios; Spantideas, Sotirios; Trakadas, Panagiotis (Frontiers in Communications and Networks, 2024)
The maritime domain is a major driver of economic growth with emerging services, comprising intelligent transportation systems (ITSs), smart ports, security and safety, and ocean monitoring systems. Sixth generation (6G) mobile networks will offer various technologies, paving the way for reliable and autonomous maritime communication networks (MCNs), supporting these novel maritime services. This review presents the main enabling technologies for future MCNs and relevant use cases, including ITSs with reduced carbon footprint, ports and maritime infrastructure security, as well as fault detection and predictive maintenance. Moreover, the current trends in integrated satellite-aerial-terrestrial-maritime network architectures are discussed together with the different network segments and communication technologies, and machine learning integration aspects.